On the morphology of the worker immatures of the leafcutter ant Atta sexdens linnaeus (Hymenoptera: Formicidae) - Solis, Daniel Russ [UNESP]; Paterson Fox, Eduardo Goncalves; Ceccato, Marcela [UNESP]; Reiss, Itamar Cristina [UNESP]; Decio, Pamela [UNESP]; Lorenzon, Natalia [UNESP]; da Silva, Natiele Goncalves [UNESP]; Bueno, Odair Correa [UNESP] (Wiley-Blackwell, 2012)
Leafcutter ants of the genus Atta Fabricius are serious agricultural pests. Morphological studies of immature stages within this group are few, and the data provided for species of considerable importance are usually incomplete. In this study, the immatures of Atta sexdens Linnaeus are described and compared using light and scanning electron microscopy. Only specimens from founding stage colonies (i.e., lacking adult workers) were used. The existence of four larval instars was estimated by a frequency plot of maximum head widths, and the larvae of different instars differed from each other mainly by their bodily dimensions. Worker larvae belonged to two distinct morphological castes: (1) gardeners and nurses and (2) within-nest generalists. The worker larvae described in this study differed from a previous description of the same species by the following traits: the existence of a genal lobe, the number of clypeal hairs, the presence of two hairs on the ninth abdominal somite, the presence of hairs on the anterior surface of the labrum, and the shape of the maxillary palpus. This study provides a comparative analysis of immature stages of A. sexdens that may be relevant to future morphological and biological studies of the Attini. Microsc. Res. Tech. 75:10591065, 2012. (c) 2012 Wiley Periodicals, Inc.
Keywords: larvae; Myrmicinae; Attini; Atta sexdens rubropilosa